Impact of Alkali Cation Identity on the Conversion of HCO3− to CO in Bicarbonate Electrolyzers. Issue 11 (1st June 2021) - Fink, Arthur G.; Lees, Eric W.; Zhang, Zishuai; Ren, Shaoxuan; Delima, Roxanna S.; Berlinguette, Curtis P.
Abstract: The reduction of CO2 to CO from a bicarbonate feedstock offers an opportunity to directly use aqueous carbon capture solutions, while bypassing ex‐situ energy‐intensive gaseous CO2 regeneration. In this study, we resolved how the electrolyte cation identity (Li +, Na +, K +, Cs + ) affects the two reactions that make bicarbonate electrolysis possible: (i) the production of in‐situ CO2 formed through reaction of HCO3 − (from the catholyte) with H + (sourced from the membrane); and (ii) the electroreduction of CO2 into CO. Our results show that cation identity does not change the rate of in‐situ CO2 formation, but it does enhance the rate of the CO2 reduction reaction (CO2RR). Electrolysis experiments performed with a constant [HCO3 − ] showed that CO selectivities progressively increased for the series Li +, Na +, K +, and Cs +, respectively. Optimization of the electrolyte composition yielded a CO selectivity of ∼80 % during electrolysis of 1.5 M CsHCO3 solutions at 100 mA cm −2, while saturated LiHCO3 solutions (0.84 M) yielded CO selectivities values of merely 30 % at the same current density. This study demonstrates a quantitative relationship between CO product selectivity and the cation radius, which provides a pathway to integrate bicarbonate electrolysis to carbon capture. Abstract : Bicarbonate electrolyzers directly convert bicarbonate‐rich carbon capture solutions into valuable products. In this work, we demonstrate that the optimization of the feedstock electrolyte by modulation of alkali cation identity and concentration enables a 26‐fold increase in CO product selectivity.